2019
DOI: 10.3390/ijms20235862
|View full text |Cite
|
Sign up to set email alerts
|

Insect Cecropins, Antimicrobial Peptides with Potential Therapeutic Applications

Abstract: The alarming escalation of infectious diseases resistant to conventional antibiotics requires urgent global actions, including the development of new therapeutics. Antimicrobial peptides (AMPs) represent potential alternatives in the treatment of multi-drug resistant (MDR) infections. Here, we focus on Cecropins (Cecs), a group of naturally occurring AMPs in insects, and on synthetic Cec-analogs. We describe their action mechanisms and antimicrobial activity against MDR bacteria and other pathogens. We report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
97
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 142 publications
(213 reference statements)
3
97
0
1
Order By: Relevance
“…31,32,34 In particular, cecropins (Cec) are a type of antimicrobial peptide with potential therapeutic applications. 38 They belong to a group of naturally occurring AMPs in insects and have exhibited in vitro activity against Grampositive and Gram-negative bacteria. 38 In this study, we investigated the in vitro antibacterial activity of a novel short synthetic CAMP derived from the ΔM2 analog of Cec D-like (CAMP-CecD) 27 against clinical strains of K pneumoniae and P aeruginosa.…”
Section: Evolutionary Bioinformaticsmentioning
confidence: 99%
“…31,32,34 In particular, cecropins (Cec) are a type of antimicrobial peptide with potential therapeutic applications. 38 They belong to a group of naturally occurring AMPs in insects and have exhibited in vitro activity against Grampositive and Gram-negative bacteria. 38 In this study, we investigated the in vitro antibacterial activity of a novel short synthetic CAMP derived from the ΔM2 analog of Cec D-like (CAMP-CecD) 27 against clinical strains of K pneumoniae and P aeruginosa.…”
Section: Evolutionary Bioinformaticsmentioning
confidence: 99%
“…Cecropin was the first AMP isolated from insects and is derived from the hemolymph of the moth Hyalophora cecropia (Hancock and Sahl, 2006). Members of the cecropin family typically have peptide chains consisting of 31-39 amino acids and possess broad-spectrum antimicrobial activities (Brady et al, 2019). Several studies have shown that cecropin, when used as a feed additive, can increase the performance of livestock and poultry while also protecting them from lethal pathogen infections (Wen and He, 2012;Wu et al, 2012;Xiao et al, 2015;Shrestha et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, AMPs gained attention as new drugs or alternate candidates over classical antibiotics to overcome the acquired multidrug resistance of microbes in clinical settings, because the targets of the AMPs are predominantly microbial membrane which allows reduced resistance compared to conventional antibiotics targeting intracellular components [ 2 , 3 ]. Several AMPs have been purified, identified, and studied from the largest class insect of arthropods in the past decades [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%